2022
DOI: 10.1021/acs.jafc.1c07727
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Response of Wheat Seedlings to Imazethapyr: From the Perspective of Fe and the Secondary Metabolite DIMBOA

Abstract: The responses of trace elements and secondary metabolites to stress can reflect plant adaptation to the environment. If and how the imperative trace element Fe and the defensive secondary metabolite 2,4-dihydroxy-7-methoxy-2H-1,4-benzoxazine-3­(4H)-one (DIMBOA) mediate the toxicity of chiral herbicides to nontarget plants remains inconclusive. We found that the herbicidal-active imazethapyr enantiomer [(R)-IM] stimulated heme oxygenase-1 activity, triggered the release of the catalytic product Fe2+, increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…This suggests that the addition of DIMBOA is more bene cial than IAA in regulating Fe valence homeostasis, which attributes to the complexation of DIMBOA with Fe 3+ and its ability to scavenge redundant free Fe ions in the organism (Hu et al 2018). The anti-Fenton and free radical elimination properties of DIMBOA-Fe can also improve the antioxidant capacity of plants (Huang et al 2022). Further study is required to more fully explore the defensive regulatory roles of auxin and DIMBOA in plant tolerance to (R)-IM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the addition of DIMBOA is more bene cial than IAA in regulating Fe valence homeostasis, which attributes to the complexation of DIMBOA with Fe 3+ and its ability to scavenge redundant free Fe ions in the organism (Hu et al 2018). The anti-Fenton and free radical elimination properties of DIMBOA-Fe can also improve the antioxidant capacity of plants (Huang et al 2022). Further study is required to more fully explore the defensive regulatory roles of auxin and DIMBOA in plant tolerance to (R)-IM.…”
Section: Resultsmentioning
confidence: 99%
“…(R)-IM was prepared according to Qian et al (Qian et al 2009) and our previous study (Huang et al 2022). DIMBOA (CAS: 15893-52-4, purity ≥ 98%) was purchased from Toronto Research Chemicals (Toronto, Canada).…”
Section: Chemicals and Experimental Designmentioning
confidence: 99%
“…29 Consequently, the application of IM in a soy−wheat rotation system is expected to influence subsequent wheat crops. 30,31 Several studies have indicated that IM would affect wheat seedlings through secondary metabolites, nutrients, and antioxidant capacity. 32,33 Given that secondary metabolites play a crucial role in mediating allelopathic interactions between plants, it is reasonable to hypothesize that herbicides, such as IM, could impact allelopathic interactions between wheat and weeds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…34 Previously, it was found that the herbicidalactive imazethapyr enantiomer [(R)-IM] stimulated HO-1 activity, triggered the release of the catalytic product Fe 2+ , and increased ROS production. 35 In animal cells, free Fe released by the Fenton reaction is rapidly isolated from the superoxide anion radical to the Fe storage protein ferritin, but this type of stress mechanism has not been demonstrated in plants. 33 In this study, the widely used broad-spectrum chiral aryloxyphenoxypropionic acid herbicide dichlorprop 36 (Figure S1) and the model plant A. thaliana were selected to evaluate the role of the HO-1 system in the pathogenesis of herbicideinduced abnormal accumulation of Fe and oxidative damage in plants.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the fate of the third component of the HO system, released Fe, in plants is almost unknown . Previously, it was found that the herbicidal-active imazethapyr enantiomer [( R )-IM] stimulated HO-1 activity, triggered the release of the catalytic product Fe 2+ , and increased ROS production . In animal cells, free Fe released by the Fenton reaction is rapidly isolated from the superoxide anion radical to the Fe storage protein ferritin, but this type of stress mechanism has not been demonstrated in plants …”
Section: Introductionmentioning
confidence: 99%